Evaluation and development of digital competence in future primary school teachers at the University of Murcia - Isabel Gutiérrez Porlán; José Luis Serrano Sánchez (Springer, 2016)
This paper presents the findings of a study carried out in the academic year 2014-2015 at the faculty of Education of the University of Murcia with first year degree students in Primary Education studying Research and ICT. The study started with the application of the DIGCOM questionnaire to analyze the digital competences of 134 students. The questionnaire served as an initial task to help students reflect on their digital competences. The subject was developed around tasks which adopted a transversal approach and used the nature of the contents itself to direct and improve students' digital competencies. Finally, the initial questionnaire was reformulated and run in order to ascertain the students' self-perception of their improvement in these competencies through the tasks they had performed. Below we present the tasks carried out, the organization of each subject and the most relevant data regarding the self-perception of digital competencies of the future primary school teachers enrolled at the University of Murcia. The data reveal, on the one hand, that the students participating consider themselves to be competent in the most basic aspects of digital competencies and, on the other, their perception that the work done in the subject has helped them quite a lot in improving their competencies.